Impact of Team (Dis)satisfaction and Psychological Safety on Performance Evaluation Biases. (February 2016) - Behfar, Kristin J.; Friedman, Ray; Oh, Se Hyung
Research on self-serving bias in teams has focused on bias after teams receive feedback. Many teams, however, work for extended periods of time before receiving feedback. This article proposes that team members exhibit biases prior to receiving feedback, depending on the level of team satisfaction. The results of two studies, one scenario study and one field study, demonstrate that members of unsatisfied teams make more self-serving claims about their contribution toward the team's task. This bias, however, is eliminated in teams with strong psychological safety norms that make team members' contributions more salient to one another. A surprising result, in our sample of ongoing teams, was that the most highly satisfied teams also demonstrated an other-centric bias—assigning more credit to other team members than to themselves.